On the effects of monetary policy shocks in developing countries - Magda Kandil (Borsa Istanbul Review, 2014)
Using annual data for a sample of developing countries, the time-series evidence indicates the allocation of monetary policy shocks, both expansionary and contractionary, between price inflation and output growth. Subsequently, cross-country regressions evaluate factors that underlie the difference in these allocations and their implications. The real effects of monetary shocks increase as the elasticity of aggregate demand increases with respect to monetary shocks. Nonetheless, capacity constraints hamper the output adjustment to monetary shocks and increase price inflation. Across countries, trend output growth increases with the output response to monetary shocks. Consistent with the stabilizing function of monetary policy, the variability of output growth decreases in the face of monetary fluctuations across countries. In contrast, monetary fluctuations increase the trend and variability of price inflation across countries.